The Role Of Traditional Games In Improving Early Childhood Social Skills - Sari, Dinar Ayu Mirunggan (MSJ : Majority Science Journal, 2025)
This study aims to describe the role of traditional games in improving early childhood social skills. The method used is library research, by collecting, studying, and synthesizing various relevant literature, such as scientific journals, books, research reports, and academic articles. Data were obtained through documentation techniques to understand the relationship between traditional games and children's social development. The results of the study show that traditional games have an important role in shaping early childhood social skills. Through this game, children learn to communicate, work together, understand the rules, and resolve conflicts positively. Additionally, interactions in traditional games help develop empathy, leadership, and confidence. Although the digital era has changed children's play patterns, traditional games still have a high educational value. Therefore, parents, educators, and the community need to preserve and reintroduce it so that children not only get pleasure in playing, but also acquire useful social skills throughout life. By incorporating traditional games into daily activities, children can grow into individuals who have high social intelligence and are able to adapt to various situations